2021
DOI: 10.3892/etm.2021.10399
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis associated with mycoplasma pneumoniae infection (Review)

Abstract: Mycoplasma pneumoniae is a common pathogen causing respiratory infections in children and adults. In addition to respiratory diseases, Mycoplasma pneumoniae is also involved in numerous extrapulmonary diseases. Thrombosis is an extrapulmonary manifestation associated with Mycoplasma pneumoniae infection. In recent years, an increasing number of case reports have been published identifying thrombosis secondary to Mycoplasma pneumoniae infection. In the present study, the available relevant literature in English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 114 publications
(140 reference statements)
0
5
0
Order By: Relevance
“…Herein, three patients (12%) had more than one distribution of embolism. One study [ 8 ] reported that the development of the cerebral infarction, abdominal organs and extremities takes 2 days to 3 weeks, 1 week to 1 month and 1–2 weeks respectively. In another study on cardiac embolism among children [ 9 ] caused by Mycoplasma pneumoniae infection, the average diagnostic time of 10 children was 13.3 days which is quite close to what we found in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, three patients (12%) had more than one distribution of embolism. One study [ 8 ] reported that the development of the cerebral infarction, abdominal organs and extremities takes 2 days to 3 weeks, 1 week to 1 month and 1–2 weeks respectively. In another study on cardiac embolism among children [ 9 ] caused by Mycoplasma pneumoniae infection, the average diagnostic time of 10 children was 13.3 days which is quite close to what we found in this research.…”
Section: Discussionmentioning
confidence: 99%
“…M. pneumoniae is associated with secondary thrombosis [7]. Previous case reports showed that pulmonary embolism [8] or splenic infarction [9] with M. pneumoniae infection occurred even without pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study by Liu et al ( 69 ), some factors contributing to thrombosis are transient, while others stem from hereditary thrombophilia in patients experiencing thrombosis due to M. pneumoniae infection. Moreover, specific transient elements, such as cold agglutinin, vascular malformations, sickle cell trait and the presence of positive antibodies such as anticardiolipin, β2-glycoprotein, lupus anticoagulant and anti-prothrombin have been proposed to elevate the risk of thrombosis ( 71 , 72 ). These factors contribute to thrombotic vessel occlusion ( 69 ).…”
Section: Mechanisms Of Extrapulmonary Manifestationsmentioning
confidence: 99%